Comparative Evaluation of Stress Acting on Abutment, Bone, and Connector of Different Designs of Acid-Etched Resin-Bonded Fixed Partial Dentures: Finite Element Analysis - Shaikh, Saquib Ahmed; Rai, Punith; Aldhuwayhi, Sami; Mallineni, Sreekanth Kumar; Lekha, Krishnapalli; Joseph, Angel Mary; Kumari, Vardharaj Vinutha; Meshramkar, Roseline (Frontiers in Bioengineering and Biotechnology, 2022)
Background: Finite element analysis (FEA) is one of the best methods for evaluating the stress distribution of restorations, such as fixed partial dentures. The development of resin cement has transformed prosthesis bonding and retention properties. Resin-bonded fixed partial dentures (RBFPD) have been considered minimally invasive treatment options for the prosthetic rehabilitation of single missing teeth. Objectives: To evaluate the stress load and distribution in four different designs of acid-etched resin-bonded fixed partial dentures using finite element analysis. Materials and Methods: The designs included standard tooth preparation principles and additional features. The first premolar and first molar abutments replaced the missing second premolar. The designs 1, 2, 3, and 4 included (1) lingual wings and occlusal rests (2) wings and proximal slices (3) wings, rests, and grooves, and (4) wings, rests, grooves, and occlusal coverage. The prepared models were restored with resin-bonded fixed partial dentures. A load of 100 N was applied to the central groove of the pontic to simulate occlusal forces. The materials used in the models were considered to be isotropic, homogenous, and linearly elastic. Finite element analysis was used to reveal stresses acting on the abutment, bone, and connector in all prosthesis designs. Results: The stresses transmitted to the abutment and bones were lowest for design 3, using wings, rests, and grooves. The stresses acting on the connector were the weakest in design 2. The stresses transmitted to the abutment and bone were highest in designs 1 and 4. The stresses transmitted to the connector were highest in design3. Conclusion: The wings, rests, and grooves design is possibly the ideal and conservative tooth preparation design to receive a posterior RBFPD. This design transmits less stress to the abutments and less bone resorption in the FEA. It is most likely to be successful in the clinical provision and ensures the longevity of the prosthesis.